2003
DOI: 10.1063/1.1542914
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the growth of 1.3 μm InAs/InGaAs dots-in-a-well structure

Abstract: The structural and optical properties of GaAs-based 1.3 μm InAs/InGaAs dots-in-a-well (DWELL) structures have been optimized in terms of different InGaAs and GaAs growth rates, the amount of InAs deposited, and In composition of the InGaAs quantum well (QW). An improvement in the optical efficiency is obtained by increasing the growth rate of the InGaAs and GaAs layers. A transition from small quantum dots (QDs), with a high density (∼5.3×1010 cm−2) and broad size distribution, to larger quantum dots with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(85 citation statements)
references
References 30 publications
4
81
0
Order By: Relevance
“…Additionally, it is clearly observed that other laser emissions have a wavelength of 1.27 µm in the O-band. Laser emission with longer wavelengths can be achieved by using novel optical gain materials such as an Sb-irradiated QD in the well (Sb-DWELL) or InAs/InGaAs QD with SSNS structures (Liu et al 2003;Yamamoto et al 2008bYamamoto et al , 2009aYamamoto et al & 2009c. These www.intechopen.com emission wavelengths are matched to the ground state of the QD structure.…”
Section: Broadband Quantum Dot Lasermentioning
confidence: 99%
“…Additionally, it is clearly observed that other laser emissions have a wavelength of 1.27 µm in the O-band. Laser emission with longer wavelengths can be achieved by using novel optical gain materials such as an Sb-irradiated QD in the well (Sb-DWELL) or InAs/InGaAs QD with SSNS structures (Liu et al 2003;Yamamoto et al 2008bYamamoto et al , 2009aYamamoto et al & 2009c. These www.intechopen.com emission wavelengths are matched to the ground state of the QD structure.…”
Section: Broadband Quantum Dot Lasermentioning
confidence: 99%
“…Since GaAs is the most commonly used capping material for InAs/GaAs QDs, the existing structural studies of buried InAs/GaAs QDs have been mainly devoted to GaAs-capped QDs. Nevertheless, different materials such as InGaAs and GaAsSb are nowadays used to cap InAs/GaAs QDs in an effort to extend its emission wavelength to the technologically interesting 1.3-155 \xm region [59][60][61][62][63][64]. For InAs/ InP QDs, capping materials other than InP, like InGaAsP, have also successfully been used for laser applications [65][66][67].…”
Section: Capping With Different Materialsmentioning
confidence: 99%
“…Capping with InGaAs has become popular in the last few years because it allows the emission wavelength of InAs/GaAs QDs [59][60][61][62][63] to be increased considerably. It is therefore very interesting to study how the structural properties of InAs QDs are affected by an InGaAs strain reducing layer.…”
Section: Ingaas Capping Of Inas/gaas Qdsmentioning
confidence: 99%
“…The second approach takes advantage of the reduction of both the confinement potential for carriers in the QDs (InGaAs barriers instead of GaAs) and the strain in the InAs QDs, yielding a redshift of the emission [2]. Several reports already showed QDs emission reaching [3] (and even going beyond [4,5]) 1.3µm by using separately one of these methods, but there are only a couple of works aimed to explore the combination of both techniques [6] to get longer wavelengths or eventually better optical properties. The main problem is that most molecular-beam epitaxy (MBE) systems have only one single In cell.…”
Section: Introductionmentioning
confidence: 99%